Understanding the Competency Levels of Art-Based Students in Utilising Technological Tools for Learning: A Case of a Digital Art Students - Randle, Oluwarotimi (CV Sinergi Ilmu dan Publikasi, 2025)
Using technology as a pedagogical teaching tool is a well-established concept, with numerous studies demonstrating its effectiveness in enhancing learning outcomes. However, few studies have explored the connection between technology and the proficiency of art-based students utilising technology for the purpose of designing and creating digital media, such as video games, comics, and animations. This study explored how facilitating conditions, prior access, and technology usage influenced the competency level of students. A quantitative descriptive approach was used to collect data from 119 students who voluntarily participated by completing an online questionnaire. Structural equation modelling was utilised to process the data obtained from the questionnaire results. The findings indicated that both computer self-efficacy and facilitating conditions had a positive effect on the perceived ease of use within a technological learning environment. This, in turn, influenced the competency of digital art students in utilising technology. Past exposure to technology influenced digital art students’ openness to experimenting with new game design and animation technologies in the technology playroom.